2015
DOI: 10.5812/jjm.8(5)2015.18573
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Campylobacter Jejuni and C. coli Isolated From Broilers Using flaA PCR-Restriction Fragment Length Polymorphism Method in Shiraz, Southern Iran

Abstract: Background:Thermophilic campylobacters, particularly Campylobacter jejuni and C. coli are the main agents of human campylobacteriosis. Campylobacter contaminated chicken products is the most important source of foodborne gastroenteritis. Evaluation of genetic diversity among Campylobacter population is critical for understanding the epidemiology of this bacterium and developing effective control strategies against Campylobacter infections and other related disorders.Objectives:The aim of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Dde I (D.I.−0.9258) was found most efficient in discriminating C. jejuni isolates as has been reported by many workers ( Hiett et al., 2006 , Khoshbakht et al., 2015 , Rajagunalan et al., 2014 , Vinueza-Burgos et al., 2017 ). The other enzymes i.e Hinf I (D.I.−0.6977) and Dpn II (D.I.−0.8427) were less discriminatory as compared to Dde I.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Dde I (D.I.−0.9258) was found most efficient in discriminating C. jejuni isolates as has been reported by many workers ( Hiett et al., 2006 , Khoshbakht et al., 2015 , Rajagunalan et al., 2014 , Vinueza-Burgos et al., 2017 ). The other enzymes i.e Hinf I (D.I.−0.6977) and Dpn II (D.I.−0.8427) were less discriminatory as compared to Dde I.…”
Section: Resultssupporting
confidence: 69%
“…Flagellin gene locus of C. jejuni contains two flagellin genes ( fla A and fla B), which are highly conserved with variable regions interspersed between them ( Khoshbakht et al., 2015 , Thomrongsuwannakij et al., 20 ). This locus is suitable for restriction fragment length polymorphism (RFLP) analysis of PCR products.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an identical pattern was observed on digestion of amplified fla A gene of C. jejuni and C. coli isolates indicating no diversity among isolates. The pattern observed in the study belong to cluster III (Pattern I) based on dendogram study of restriction profiles of fla A gene of virulent strains of C. jejuni and C. coli reported by workers (Khoshbakht, Tabatabaei, Hosseinzadeh, Shirzad, & Seifi, ). Of the various restriction enzymes, Alu I, Dde I, Hin fI, Eco RI, and Pst I enzymes used for RE studies, Hin fI is not able to discriminate clearly among the isolates, whereas Alu I produces bands that are too small to be analyzed.…”
Section: Discussionmentioning
confidence: 60%
“…(5-CTATTTTATTTTTGAGTGCTTGTG-3) and reverse primers (5-GCTTTATTTGCC ATTTGTTTTATTA-3) (Khoshbakht et al, 2015).…”
Section: Genotypic Confirmation Of Isolates By Polymerase Chain Reaction For Hip O Gene and Map Agenementioning
confidence: 99%